Redes de comunicação: metodologias coletivistas para o planejamento da transição agroecológica, com comunidades camponesas em Nariño, Colômbia - González Méndez, Daniel Ricardo (2025)
In the face of evident inequality and socio-ecological annihilation in the Global South, stemming from the economic powers that drive the capitalist, imperialist, patriarchal, supremacist, and extractivist systems with direct impacts on rural areas, this research was born. It brings the territorial planning of peasant communities in Colombia to the discussion and practice. From an agroecological perspective, the goal was to establish social communication networks between the peasant communities of La Tulpa and Nodo de Agroecología de Tango and extension technicians. This would enable dialogue and the collective development of strategies for planning and implementing proposals that promote emancipatory agroecology. These proposals aim to foster community autonomy in their territories and ecosocial relationships with other stakeholders and nature, focusing on integral well-being. The researchers applied a co-created methodology based on developing concrete projects through various activities, using social techniques and technologies for reflection and constructing plans to strengthen the agroecological transition of these communities. This approach was linked to an analysis of the departmental public policy on agroecology.